Circadian acclimatization of performance, sleep, and 6-sulfatoxymelatonin using multiple phase shifting stimuli - Youngstedt, Shawn D.; Elliott, Jeffrey; Patel, Salma; Zi-Ching Mak, Natalie; Raiewski, Evan; Malek, Elias; Strong, Michael; Mun, Chung Jung; Peters, Tyler; Madlol, Remun; Tasevska, Natasha; Rasoul, Massiullah; et al. (Frontiers in Endocrinology, 2022)
Misalignment between the environment and one’s circadian system is a common phenomenon (e.g., jet lag) which can have myriad negative effects on physical and mental health, mental and physiological performance, and sleep. Absent any intervention, the circadian system adjusts only 0.5-1.0 h per day to a shifted light-dark and sleep-wake schedule. Bright light facilitates circadian adjustment, but in field studies, bright light is only modestly better than no stimulus. Evidence indicates that exercise and melatonin can be combined with bright light to elicit larger shifts but no study has combined all of these stimuli or administered them at the times that are known to elicit the largest effects on the circadian system. The aims of this study are to compare the effects of different treatments on circadian adjustment to simulated jet lag in a laboratory. Following 2 weeks of home recording, 36 adults will spend 6.5 consecutive days in the laboratory. Following an 8 h period of baseline sleep recording on the participant’s usual sleep schedule on Night 1 (e.g., 0000-0800 h), participants will undergo a 26 h circadian assessment protocol involving 2 h wake intervals in dim light and 1 h of sleep in darkness, repeated throughout the 26 h. During this protocol, all urine voidings will be collected; mood, sleepiness, psychomotor vigilance, and pain sensitivity will be assessed every 3 h, forehead temperature will be assessed every 90 min, and anaerobic performance (Wingate test) will be tested every 6 h. Following, the circadian assessment protocol, the participant’s sleep-wake and light dark schedule will be delayed by 8 h compared with baseline (e.g., 0800-1400 h), analogous to travelling 8 times zones westward. This shifted schedule will be maintained for 3 days. During the 3 days on the delayed schedule, participants will be randomized to one of 3 treatments: (1) Dim Red Light + Placebo Capsules, (2) Bright Light Alone, (3) Bright Light + Exercise + Melatonin. During the final 26 h, all conditions and measures of the baseline circadian protocol will be repeated. Acclimatization will be defined by shifts in circadian rhythms of aMT6s, psychomotor vigilance, Wingate Anaerobic performance, mood, and sleepiness, and less impairments in these measures during the shifted schedule compared with baseline. We posit that Bright Light Alone and Bright Light + Exercise + Melatonin will elicit greater shifts in circadian rhythms and less impairments in sleep, mood, performance, and sleepiness compared with Dim Red Light + Placebo Capsules. We also posit that Bright Light + Exercise + Melatonin will elicit greater shifts and less impairments than Bright Light Alone.